Efficacy and tolerability of a hyaluronic acid‐based serum and a peptide‐rich cream for the face and neck in subjects with photodamaged skin. (1st June 2022) - Gold, Michael H.; Biron, Julie A.; Wilson, April; Nelson, Diane B.
Abstract: Background: Barrier properties of the stratum corneum inhibit delivery of topical ingredients containing large molecules to desired targets in the skin. This study evaluated the efficacy and tolerability of a skincare regimen comprised of a hyaluronic acid‐based serum (InF‐HA) and a peptide‐rich cream (InF‐PEP) containing large molecular ingredients designed to improve the appearance and overall quality of skin. Methods: This 12‐week study evaluated changes from baseline in skin tone, skin texture, and lines/wrinkles (6‐point grading scale) of twice‐daily application of a two‐part skincare regimen to the face and neck in female subjects with mild to moderate photodamage. Subject satisfaction was assessed, and Adverse Events (AEs) were captured throughout. Results: Seventeen subjects with a mean age of 52 years completed the study. Improvements from baseline in the appearance of facial skin texture (79%), lines/wrinkles (50%), and skin tone (44%) occurred at week 12. Improvements in neck appearance from baseline were demonstrated in skin texture (68%), skin tone (48%), and lines/wrinkles (36%). No AEs occurred related to the use of study products. All subjects reported an overall improvement in the appearance of their skin and that their skin looked and felt smoother; 88% reported their skin looked more radiant, and 82% reported their skin looked firmer. Conclusions: Application of a skincare regimen comprised of an HA‐based serum and a peptide‐rich cream led to substantial improvements in skin texture, skin tone, and lines/wrinkles on the face and neck over 12 weeks. Both products were well‐tolerated with a high level of subject satisfaction.